The traditional Chinese medicine formulation Ruanjian Sanjie Decoction regulates the tumor matrix and improves the anti-tumor efficacy of TP-PEG-LPs (Brazilian Journal of Pharmaceutical Sciences, 2019)
The Ruanjian Sanjie Decoction (RSD) is a traditional Chinese medicine (TCM) formulation consisting of Spica Prunellae, Pseudobulbus Cremastrae Seu Pleiones, Concha Ostreae and Semen Coicis, and widely used as an adjuvant in anti-cancer therapy. The aim of this study was to determine the effects of RSD on the extracellular matrix (ECM) of tumors, and on the efficacy of anti-cancer nano-formulations in a tumor-bearing mouse model. The mice were treated with triptolide encapsulated in PEG-modified liposomes (TP-PEG-LPs), either alone or in combination with RSD. The combination treatment significantly retarded tumor growth relative to the untreated controls, indicating the potent adjuvant effect of RSD in targeted anti-cancer therapy. In addition, RSD also reduced the amount of total collagen and collagen I and increased that of collagen III in the tumor ECM, along with decreasing the expression of the pro-angiogenic VEGF. Finally, even high doses of RSD did not significantly affect the liver and kidney function or body weight, indicating low toxicity.